Tingkat Kepatuhan Pengobatan pada Pasien Prolanis Diabetes Melitus Tipe 2 di Klinik Jatisari Karawang Periode bulan Januari – Maret 2021 - Aliyana Aliyana; Meiti Rosmiati (Jurnal Health Sains, 2021)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia that occurs due to defects in insulin secretion, insulin action or both. Half-life is very important, especially in long-term treatment in order to achieve therapeutic success. As in the Hadith narrated by Muslim. That every disease has a cure. Then the drugs used obediently will help the patient's condition get better. In the management of the disease, the role of the patient becomes very important, especially in terms of increasing adherence to therapy in order to achieve optimal blood glucose levels to prevent more severe complications. The purpose of this study was to describe the level of treatment of patients with diabetes mellitus prolanis at  Jatisari Clinic in the period from January to April 2021. The type of research conducted an observational study using a descriptive method. Sampling using a total sampling technique with a sample of 99 patients. The primary data collection instrument used a Morisky Medication Adherence Scale 8 items (MMAA-8) questionnaire find the level of adherence therapy in Diabetes Mellitus patients. The results of the study found that the level of adherence to treatment in patients with diabetes mellitus prolanis at  Jatisari Clinic according are "High Adherence" , “Medium Adherence”, and “ Low Adherence” with 33 patients (33.33%) , 43 patients (43.44%)  and 23 patients (23.22%) respect ively